PENGARUH BRAND AWARENESS DAN KUALITAS PRODUK TERHADAP MINAT BELI ULANG DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA SEAFOOD SITUBONDO - Herawati, Anjanis Dewi; Arief, Mohammad Yahya; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2023)
Marketing is one of the important factors in the company, so marketing is the heart of the company's life. This study aimed to determine brand awareness and product quality on customer satisfaction with repurchase interest in Seafood Situbondo. The population in this study are all consumers who have consumed or customers who have stopped by Seafood Situbondo. The sampling method is random (simple random sampling) with a total sample of 96. Data analysis and hypothesis testing in research using the Structural-Partial Least square equation model (PLS-SEM). The results of direct influence hypothesis testing using the Smart PLS3.0 application show that brand awareness has a significant effect on customer satisfaction, product quality has a significant effect on customer satisfaction, Brand awareness has an insignificant effect on repurchase interest, product quality has a significant effect on repurchase interest, customer satisfaction has a significant effect on repurchase interest, Brand awareness has a significant effect on repurchase interest through customer satisfaction, product quality has a significant effect on repurchase interest through customer satisfaction.